Performa Antena Directional dan Omnidirectional pada Sistem FPV Walksnail Avatar - Peksi Branjangan, Panji; Ridwan, Dhendy Zaki (Politeknik Negeri Malang, 2025)
Visual monitoring in heavy equipment operations was critical for reducing workplace accidents caused by operator blind spots. Conventional static cameras and sensors often failed to provide adequate coverage in dynamic environments, leading to limitations in situational awareness. This study aimed to evaluate the transmission performance of the Walksnail Avatar digital FPV system using directional and omnidirectional antennas for blind spot monitoring applications. An experimental method was employed by configuring a digital FPV transmitter and receiver at a fixed distance of 20 meters with a wooden obstacle placed along the transmission path. The receiver antenna orientation was rotated at 10-degree intervals to measure variations in data rate and latency. Two antenna configurations were tested: a 9.4 dBi directional patch antenna and a standard omnidirectional antenna. The results indicated that the directional patch antenna achieved a maximum data rate of 25 MBps at frontal orientations but experienced significant degradation at lateral angles, with latency increasing up to 100 ms. In contrast, the omnidirectional antenna demonstrated more uniform performance across all directions, maintaining data rates between 19–24 MBps and stable latency below 45 ms. These findings were consistent with antenna radiation theory regarding gain concentration and angular coverage.The study implied that omnidirectional antennas were more suitable for blind spot monitoring in heavy equipment operations due to their consistent coverage and low latency, while directional antennas were better applied for focused line-of-sight monitoring scenarios. The results provided empirical guidance for selecting antenna configurations in digital FPV-based industrial safety systems.